Electric field‐assisted preparation of PANI/TPU all‐organic composites with enhanced dielectric permittivity and anisotropic optical properties. Issue 12 (26th September 2022) - Wu, Weifei; Ren, Tianli; Liu, Xueqing; Huai, Kai; Cui, Xin; Wei, Huaixiao; Hu, Jinjin; Xia, Yuming; Huang, Shuohan; Fu, Kun (Kelvin); Zhang, Jianming; Chen, Yuwei
Abstract: To meet the demands of multifunctional applications, developing functional composites with excellent properties (such as high dielectric permittivity, good mechanical properties, and anisotropic optical transmittance) is urgent. In this regard, preparing composites with all‐organic components is a promising strategy. Herein, we demonstrated a simple and time‐saving method for assembling and aligning polyaniline (PANI) particles in the TPU matrix by an AC electric field. The alignment of PANI in the polymer matrix not only obviously enhances dielectric permittivity but also effectively increases optical anisotropy. At the same filler loading content, the dielectric permittivity of aligned composites prepared under 10 Hz electric fields is 10.63 (10 −1  Hz), which is higher than the dielectric property of random composites (8.58). The kinetics of aligning process of PANI particles are systematically studied by in situ optical microscope while an AC electric field is applied. We believe that this research work provides a potential solution to increase both dielectric permittivity and optical anisotropy of composites by the alignment of organic fillers via an electric field, which is essential for future flexible wearable electronics. Abstract :